THE DUSUN TINDAL RESIDENTS OF LASAU TINTAPON IN KOTA BELUD, SABAH, A TRADITION OF USING ARTEFACT TAJAU - Noria, Tugang; Benigel Royce, Banaas; Alvine, Natus; Maxwilliam Andy, Gagat (UNIMAS Publisher, 2021)
This research looked into the use of artefact tajau as one of the Dusun Tindal counting traditions. In addition, this report will clarify how this native used the term tajau a century ago. This research also employs a qualitative approach fieldwork method with sources being interviewed to gather evidence. The researcher was taken to the study site by an informant who is an expert and a traditional chief in the village. This approach is employed so that the researcher can analyze and comprehend the study’s use of the tajau in greater detail. Futhermore, this research demonstrates that tajau has been used since the first war until the present century.